The long noncoding RNA LAL contributes to salinity tolerance by modulating LHCB1s’ expression in Medicago truncatula - Yang Zhao; Yafei Liu; Feiran Zhang; Zeng-Yu Wang; Kirankumar S. Mysore; Jiangqi Wen; Chuanen Zhou (Communications Biology, 2024)
Abstract Long non-coding RNAs (lncRNAs) are abundant in plants, however, their regulatory roles remain unclear in most biological processes, such as response in salinity stress which is harm to plant production. Here we show a lncRNA in Medicago truncatula identified from salt-treated Medicago truncatula is important for salinity tolerance. We name the lncRNA LAL, L ncRNA A NTISENSE to M. truncatula L IGHT-HARVESTING CHLOROPHYLL A/B BINDING (MtLHCB) genes. LAL is an antisense to four consecutive MtLHCB genes on chromosome 6. In salt-treated M. truncatula, LAL is suppressed in an early stage but induced later; this pattern is opposite to that of the four MtLHCBs. The lal mutants show enhanced salinity tolerance, while overexpressing LAL disrupts this superior tolerance in the lal background, which indicates its regulatory role in salinity response. The regulatory role of LAL on MtLHCB1.4 is further verified by transient co-expression of LAL and MtLHCB1.4-GFP in tobacco leaves, in which the cleavage of MtLHCB1.4 and production of secondary interfering RNA is identified. This work demonstrates a lncRNA, LAL, functioning as a regulator that fine-tunes salinity tolerance via regulating MtLHCB1s’ expression in M. truncatula.